Long-term reprogramming of primed microglia after moderate inhibition of CSF1R signaling. - León-Rodríguez, Ana; Mateos-Grondona, Jesús; Marín Wong, Sonia; López-Aranda, Manuel Francisco; López-Ávalos, María Dolores (Wiley, 2024)
In acute neuroinflammation, microglia activate transiently, and return to a resting state later on. However, they may retain immune memory of such event, namely priming. Primed microglia are more sensitive to new stimuli and develop exacerbated responses, representing a risk factor for neurological disorders with an inflammatory component. Strategies to control the hyperactivation of microglia are, hence, of great interest. The receptor for colony stimulating factor 1 (CSF1R), expressed in myeloid cells, is essential for microglia viability, so its blockade with specific inhibitors (e.g. PLX5622) results in significant depletion of microglial population. Interestingly, upon inhibitor withdrawal, new naïve microglia repopulate the brain. Depletion-repopulation has been proposed as a strategy to reprogram microglia. However, substantial elimination of microglia is inadvisable in human therapy. To overcome such drawback, we aimed to reprogram long-term primed microglia by CSF1R partial inhibition. Microglial priming was induced in mice by acute neuroinflammation, provoked by intracerebroventricular injection of neuraminidase. After 3-weeks recovery, low-dose PLX5622 treatment was administrated for 12 days, followed by a withdrawal period of 7 weeks. Twelve hours before euthanasia, mice received a peripheral lipopolysaccharide (LPS) immune challenge, and the subsequent microglial inflammatory response was evaluated. PLX5622 provoked a 40%–50% decrease in microglial population, but basal levels were restored 7 weeks later. In the brain regions studied, hippocampus and hypothalamus, LPS induced enhanced microgliosis and inflammatory activation in neuraminidaseinjected mice, while PLX5622 treatment prevented these changes. Our results suggest that PLX5622 used at low doses reverts microglial priming and, remarkably, prevents broad microglial depletion.
Keywords: Microglia - Investigación; Sistema nervioso - Enfermedades; CSF1R; Microglia; Neuroinflammation; PLX5622; Priming